Development of computer program for analyzing thick and laminated plate -shell assemblages by using composite / Senin S.F. and Keong K.C. - S.F., Senin; Keong, K.C. (2006)
A new formulation on general shell theory has been proposed to accommodate the shear deformation effect and inertia effects are included. The analysis capability of the formulation is the vibration analysis of a thick and laminated plate-shell assemblages using composite. The proposed general shell formulation can be used for thick shell and can be converted to thin shell by neglecting the thickness-to-radius ratio.